FIRST RECORD OF SIMOSAURUS (SAUROPTERYGIA, NOTHOSAUROIDEA) FROM THE CARNIAN (LATE TRIASSIC) OF ITALY - FABIO M. DALLA VECCHIA (Rivista Italiana di Paleontologia e Stratigrafia, 2008)
The nothosauroid sauropterygian Simosaurus is reported for the first time both from Italy and from the early Carnian (earliest Late Triassic). Diagnostic dorsal neural arches and clavicles as well dorsal ribs have been collected in the Rio dal Lago Formation near Dogna (Friuli). Purported Simosaurus remains from the Ladinian of Austria cannot be attributed to this genus with certainty and the presence of additional articular structures in the dorsal neural arch ("infraprezygapophyses" and infrapostzygapophyses) cannot distinguish Simosaurus from Bobosaurus if the craniocaudal polarity or other vertebral features are unknown.